2019
DOI: 10.1103/physrevaccelbeams.22.074701
|View full text |Cite
|
Sign up to set email alerts
|

Electron radiography with different beam parameters using laser plasma accelerator

Abstract: An experimental study on the radiography of various metallic and biological plant samples with a minimum resolution of ∼75 μm using relativistic electron beams from the laser plasma accelerator is presented. Electron beams were generated from the interaction of Ti:sapphire laser pulses of 120 fs duration with underdense plasma of 4 mm length, created using Ar and He gas jets, with two different parameters, i.e., a maximum energy of ∼50 MeV (broad spectrum) and a quasimonoenergetic beam with a peak energy of ∼1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…8 c & d). This suggests increasing role of wakefield towards higher density leading to a hybrid acceleration regime [66,71]. The above observations are also supported by the fact that the present experimental condition of L~λ p and P ~P c may not support strong self-modulation of the laser pulse and hence generation of strong wakefield.…”
Section: (B) 2d Pic Simulation Verification Of Acceleration Mechanismssupporting
confidence: 57%
See 3 more Smart Citations
“…8 c & d). This suggests increasing role of wakefield towards higher density leading to a hybrid acceleration regime [66,71]. The above observations are also supported by the fact that the present experimental condition of L~λ p and P ~P c may not support strong self-modulation of the laser pulse and hence generation of strong wakefield.…”
Section: (B) 2d Pic Simulation Verification Of Acceleration Mechanismssupporting
confidence: 57%
“…Further, through detailed PIC simulations it was shown that DLA can double the energy of accelerating electrons over wakefield [67][68][69][70]. In our recent investigations also, we identified pure DLA and hybrid regime of acceleration in pure N 2 and He + N 2 mixed gas target for similar condition of L>λ p [71]. Role of DLA in laser plasma acceleration is a subject of current investigation.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…[ 18 ] High energy electron radiography through laser plasma acceleration with wakefield method or direct laser acceleration method at 100 MeV is attained, which has 100 μm range resolution. [ 19–21 ] But for the high energy electron radiography from laser‐driven plasma accelerators, the pointing and spectra stability of electron bunch in the previous experiment could not maintain within several shots. The stable electron beams on spectra and direction have been achieved in our experiments and used to direct imaging.…”
Section: Introductionmentioning
confidence: 99%